Fostering Teachers’ Empathy and Inclusion in Israeli Society - Shapira, Noa; Dolev, Niva (International Journal of Multicultural Education, 2023)
In this study that draws from the fields of Social Psychology and Multicultural Education, 45 Arab and Jewish pre-service and 108 Arab and Jewish in-service teachers were presented with a program designed to foster intergroup empathy and inclusive views. The two groups went through a similar process: choosing their outgroup, finding media that presented their outgroup’s narratives, and reflecting on the experience. This study used mixed methods, including content analysis of the teacher’s reflections. The findings indicate that mediated contact is an essential element of the empathy-enhancing process and that the narrative approach evokes expressions of empathy and inclusion. Differential outcomes between teachers were observed, which can clarify the process effects and how they foster empathy and inclusion.